Clinical Efficacy of the Multilayered Skull Base Reconstruction Using In Situ Bone Flap in Endoscopic Endonasal Approach for Craniopharyngioma - Zhou, Yuefei; Hei, Yue; Soto, Jose M.; Jin, Tao; Jiang, Xiaofan; Feng, Dongxia; Liu, Weiping; Gao, Dakuan (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective The aim of the study is to summarize and analyze the efficacy of the multilayered skull base reconstruction using in situ bone flap in endoscopic endonasal approach (EEA) for craniopharyngiomas.Methods A retrospective review of 65 patients who underwent resection of their histopathology confirmed craniopharyngiomas performed at a single institution. Based on the team's understanding and mastery of skull base reconstruction techniques, patients were divided into two groups according to the methods of reconstruction in two periods. First (March 2015 through August 2016), osseous reconstruction was not adopted and served as the control group (34 cases). Second (September 2016 through July 2019), in situ bone flap repair of the skull base (complete osseous reconstruction) served as observation group (31 cases). The length of hospitalization and nasal exudation, bed rest time of hospital discharge, the incidence of cerebrospinal fluid leaks, lumbar drainage, and intracranial/pulmonary infections were collected and compared.Results Compared with the control group, patients in the observation group had obviously less lumbar drainage and CSF leakage (p < 0.05), but had no significant difference in cases of re-operation, meningitis, and pulmonary infection. At the meantime, cases of nasal exudation, bed rest, and hospitalization of the observation group were significantly reduced (p < 0.05) in the observation group.Conclusion The multilayered reconstruction technique (especially using in situ bone flap, combined with vascularized pedicled nasoseptal flap) is a safe and effective method in achieving watertight closure after EEEA, and can significantly reduce the incidence of cerebrospinal fluid leaks, and facilitate rehabilitation in skull base reconstruction of craniopharyngiomas.
Keywords: extended endoscopic endonasal approach; craniopharyngioma; skull base reconstruction; multilayer; CSF leak